Deteksi Bakteri Coliform Dan Escherichia coli Pada Depot Air Minum Isi Ulang Di Kota Pasangkayu Kabupaten Mamuju Utara Sulawesi Barat - Hasriani Hasriani; Muhammad Alwi; Umrah Umrah (Biocelebes, 2013)
This research entitle "Detect the bacterium of Coliform and Escherchia coli at depot of drinking water refill the diKota Pasangkayu of Sub-Province of Mamuju of North of West Sulawesi" have been executed in March until May 2013, in Biological Laboratory of Biological Majors Base of Faculty MIPA Tadulako University Palu. Target of this research to detect the bacterium of Coliform and Escherchia coli at depot of drinking water refill in Town of Pasangkayu of Sub-Province Mamuju North West Sulawesi and also determine the quality by mikrobiologis pursuant to Standard of Indonesia National (SNI). Method used in this research is Most Probable Number (MPN). Result of Research indicate that at fifth of depot which have in test, that is at test of MPN Coliform of there is three depot which are positive namely depot B for the BI OF standard water with the value 4 MPN/100 mL sampel, for the depot of C namely standard CI water with the value 150 MPN/100 mL sampel, CII irrigate the process by niali 23 MPN/100 mL sampel, CIII irrigate the gallon with the value MPN 21 MPN/100 mL sampel, while for the depot of D namely IN standard water show the value MPN 43 MPN/100 mL sampel. Pursuant to examination of Coliform Fecal and Escherchia coli expressed by all sampel is negativity. Keywords: Coliform, Escherchia Coli, and Drinking water refill.